2020
DOI: 10.31611/ch.73
|View full text |Cite
|
Sign up to set email alerts
|

New dietary records for the Cuban Spotted Red Trope, Tropidophis maculatus (Squamata: Tropidophiidae)

Abstract: Tropidophis maculatus (Bibron, 1840) is a mesophilic snake inhabiting forest patches and open secondary scrub savannas in western and central Cuba (Schwartz & Henderson 1991; Rodríguez et al. 2013). The only dietary records for this species are the lizards Anolis angusticeps and A. alutaceus, for individuals from Havana city (Collette 1961). Herein we provide new data on the diet of wild T. maculatus. On 17 April 2010, we found a juvenile female Tropidophis maculatus (140 mm SVL) at Soroa (22.7960, -83.006… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
4
2
0
Order By: Relevance
“…Because anoles tend to sleep on perches above ground level, both in plants and in human-made structures such as buildings, fence mesh, and barbed wire, the Spotted Red Trope probably found its prey using an active foraging strategy. This coincides with comments in Díaz and Cádiz (2020) and Rodríguez-Cabrera et al (2020a, 2020c, who described this species as a climbing, semi-arboreal snake.…”
Section: T a B L E O F C O N T E N T S F E A T U R E A R T I C L E Ssupporting
confidence: 90%
“…Because anoles tend to sleep on perches above ground level, both in plants and in human-made structures such as buildings, fence mesh, and barbed wire, the Spotted Red Trope probably found its prey using an active foraging strategy. This coincides with comments in Díaz and Cádiz (2020) and Rodríguez-Cabrera et al (2020a, 2020c, who described this species as a climbing, semi-arboreal snake.…”
Section: T a B L E O F C O N T E N T S F E A T U R E A R T I C L E Ssupporting
confidence: 90%
“…Our observation of the individual from the "María La Gorda" Resort corroborates statements in Díaz and Cádiz (2020) and Rodríguez-Cabrera et al (2020a, 2020c) that this species readily climbs. In this case, the snake was on a wooden handrail, similar to conspecifics observed on vegetation in more natural areas (Rodríguez-Cabrera et al 2020a, 2020c.…”
Section: O N S E R V At I O N a N D N At U R A L H I S T O R Ysupporting
confidence: 87%
“…Our observation of the individual from the "María La Gorda" Resort corroborates statements in Díaz and Cádiz (2020) and Rodríguez-Cabrera et al (2020a, 2020c) that this species readily climbs. In this case, the snake was on a wooden handrail, similar to conspecifics observed on vegetation in more natural areas (Rodríguez-Cabrera et al 2020a, 2020c. These actively foraging snakes feed primarily on sleeping anoles that are captured at night (Collette 1961;Rodríguez-Cabrera et al 2020a, 2020cRodríguez-Cabrera and Hernández Gómez 2021).…”
Section: O N S E R V At I O N a N D N At U R A L H I S T O R Ysupporting
confidence: 87%
See 1 more Smart Citation
“…This fire ant is invasive in Cuba, and no evaluation of damage to human and/or native fauna has been studied. Rodríguez-Cabrera et al (2020) reported fire ants in the stomach of the snake Tropidophis maculatus (Bibron, 1840), but due to the low number of ants, this consumption seemed to have been accidental. The intentional consumption of this ant was detected in frogs (García-Padrón and Borrego in press, LYGP unpubl.…”
Section: Stomach Contentsmentioning
confidence: 99%